PERCEIVED ORGANIZATIONAL SUPPORT, SERVANT LEADERSHIP AND PSYCHOLOGICAL CAPACITY RELATIONSHIP - Baykal, Elif; Zehir, Cemal (FUTURE ACAD, 2019)
Servant leadership is one of the most prominent contemporary leadership styles famous for improving ethical culture in modern companies. Its contributions in promoting more morality-centered work atmospheres and more collaborative and harmonious organizations make many researchers focus their lenses on the subject. It is a special form of leadership that includes a specific focus on followers as well as all the other related stakeholders. It has a tendency to focus on others' needs, with the goal of helping them grow and develop. In this study it is proposed that servant leadership style will be effective on psychological capacities of individuals and perceived organizational support will have a mediating effect in this relationship. To test propositions of this study, a field survey using questionnaires was conducted on 176 companies and we applied 815 usable surveys. The data obtained from the field study has been analysed by SPSS statistical packaged software. After analysing validities and reliabilities of the measures, a series of regression analysis was conducted to test the hypotheses. Results of the study confirmed the propositions regarding the relationships among the servant leadership, psychological capital and perceived organizational support Findings of the study are consistent with the propositions that perceived organizational support acts as a mediator in the relationship between servant leadership and psychological capital. (C) 2019 Published by Future Academy www.FutureAcademy.org.UK
Keywords: Servant leadership; psychological capacity; perceived organizational support; positive psychological behaviour; AUTHENTIC LEADERSHIP; EMPLOYEE PERFORMANCE; BEHAVIOR; CLIMATE; IMPACT; SCALE; Business & Economics